ACUTE TOXICOLOGICAL EvALUATION OF THE AQUEOUS EXTRACT OF ECLIPTA ALBA HAssK (Biological Sciences - PJSIR, 2001)
Acute toxicological evaluation of Eclipta alba, Hassk, was carried out on albino mice through oral, parenteral and systemic routes. The severity and depth of toxicities exhibited by either route were found to be dose dependent. The aqueous extract of E alba exhibited a marked action on the central nervous system. LD50 as calcul ated for oral, intravenous and intraperitoneal routes were 7.841 g kg·1, 302.8 and 328.3 mg kg·1 respectively . An aqueous extract of E. alba                                                                                                                                                                                                                                   •was found to be safe and non-toxic  at a dose of 2.0 g kg·1   for oral and 200 mg kg·1 for intravenous  and intraperitonealroutes.